Migration, Human Capital, and Poverty in a Dual-Economy Model of a Developing Country - Masson, Paul (IMF Working Papers; Working Paper ;, 2001)
The coexistence of urban and rural poverty and migration to cities is studied in a dual economy model where the acquisition of skills is costly and involves migration to urban areas. In this model, both the distribution of innate abilities and the distribution of wealth matter for the migration decision, and costs of backmigration may produce an urban poverty trap if unemployment lowers household wealth below the cost of skills acquisition.